Cover Image. Issue 7 (5th July 2018) - Li, Ye; Fang, Yuxing; Wang, Xiaoying; Song, Luping; Huang, Ruiwang; Han, Zaizhu; Gong, Gaolang; Bi, Yanchao
Abstract : COVER ILLUSTRATION The cartoon shows that Confucius (left) is teaching his students (right). The text is a citation of The Analects of Confucius . It means that "The Master knows admirably how to lead people on step by step. He has enlarged my mind with an extensive knowledge of the arts, while guiding and correcting my judgement and taste. Thus I could not stop in my progress, even if I would." The light spectrum behind the text implies the application of functional near infra‐red spectroscopy technique to the field of teaching in a naturalistic context.